Body Image, Orgasmic Response, and Sexual Relationship Satisfaction: Understanding Relationships and Establishing Typologies Based on Body Image Satisfaction. Issue 4 (26th July 2020) - Horvath, Zsolt; Smith, Betina Hodt; Sal, Dorottya; Hevesi, Krisztina; Rowland, David L.
Abstract: Introduction: This study explored the role of body image dissatisfaction on orgasmic response during partnered sex and masturbation and on sexual relationship satisfaction. The study also described typologies of women having different levels of body image satisfaction. Methods: A sample of 257 Norwegian women responded to an online survey assessing body image dissatisfaction, problems with orgasm, and sexual relationship satisfaction. Using structural equation modeling and factor mixture modeling, the relationship between body image dissatisfaction and orgasmic response was assessed, and clusters of sexual response characteristics associated with varying levels of body image dissatisfaction were identified. Main Outcome Measure: Orgasmic function during partnered sex and masturbation, along with sexual relationship satisfaction, were assessed as a function of body image. Results: Body image dissatisfaction, along with a number of covariates, predicted higher levels of "problems with orgasm" during both partnered sex and masturbation, with no significant difference in the association depending on the type of sexual activity. Varying levels of body image dissatisfaction/satisfaction were associated with differences in orgasmic incidence, difficulty, and pleasure during partnered sex; with one orgasmic parameter during masturbation; and with sexual relationship satisfaction. Conclusion: Body image dissatisfaction and likely concomitant psychological distress are related to impaired orgasmic response during both partnered sex and masturbation and may diminish sexual relationship satisfaction. Women with high body image dissatisfaction can be characterized by specific sexual response patterns.